2012
DOI: 10.1177/0040517512449049
|View full text |Cite
|
Sign up to set email alerts
|

Objective evaluation of fabric pilling based on wavelet transform and the local binary pattern

Abstract: A new objective fabric pilling evaluation method based on wavelet transform and the local binary pattern (LBP) is developed. The surface pills are identified from the high-frequency noise, fabric texture, and illuminative variation of a pilled fabric image by the two-dimensional discrete wavelet transform. The energies of each detailed sub-image at scales 4–6 in three orientations (horizontal, vertical, and diagonal) and the LBP features of the reconstructed detail image from scales 3 to 6 are calculated as el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…For example, prediction of fabric elongation, 25 drying times of bobbins, 4 fabric pilling, 39 the air permeability of fabrics. 15 • Construction of models to reduce the consumption of textile-related materials, such as fabrics, yarns, dyes, and sewing threads 5 • Discovering patterns that can be used to produce better textile endproducts 13,61,68 • Analyzing textile data to achieve better customer satisfaction…”
Section: Advantages Of Dm Enabled In Textile Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, prediction of fabric elongation, 25 drying times of bobbins, 4 fabric pilling, 39 the air permeability of fabrics. 15 • Construction of models to reduce the consumption of textile-related materials, such as fabrics, yarns, dyes, and sewing threads 5 • Discovering patterns that can be used to produce better textile endproducts 13,61,68 • Analyzing textile data to achieve better customer satisfaction…”
Section: Advantages Of Dm Enabled In Textile Industrymentioning
confidence: 99%
“…33,35 Another technical difficulty in textile studies is to determine independent parameters from the training data to reduce the dimensionality of the feature vector, improving the speed of the evaluation and accuracy through this way. To solve this problem, several textile studies 35,39,40 used the PCA technique.…”
Section: Support Vector Machine In Textile Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…The results of their study indicated that the ANN had a high prediction rate for woolen fabrics. Jing et al [22] developed a predictive model for the wrinkling appearance of fabric using modified wavelet coefficients and optimized SVM classifications.…”
Section: Related Workmentioning
confidence: 99%
“…The wavelet transform not only contains the localization idea of short time Fourier transform, but also overcomes the defect that the window size cannot vary with frequency. The resolution is good at high and low frequencies; it is an ideal signal processing mode [21].…”
Section: Wavelet Theorymentioning
confidence: 99%